2020
DOI: 10.3389/fbioe.2020.00937
|View full text |Cite
|
Sign up to set email alerts
|

Aligned Fingolimod-Releasing Electrospun Fibers Increase Dorsal Root Ganglia Neurite Extension and Decrease Schwann Cell Expression of Promyelinating Factors

Abstract: Fingolimod-Releasing Biomaterial Fibers fingolimod-loaded fibers enhanced neurite outgrowth from whole and dissociated DRG neurons, increased Schwann cell migration, and reduced the Schwann cell expression of promyelinating factors. The in vitro findings show the potential of the aligned fingolimod-releasing electrospun fibers to enhance peripheral nerve regeneration and serve as a basis for future in vivo studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 74 publications
1
11
0
Order By: Relevance
“…For this reason, in this study for the first time to our knowledge, electrospun ha-PLGA scaffolds, designed for tendon TE, were subjected to hydrolytic degradation under di-H 2 O and PBS conditions at 37 • C and evaluated for up to 20 weeks. Of note, tendons regenerate at a slow healing rate, which necessitated performing the degradation study up to 20 weeks, compared to most other studies that usually conducted similar experiments on electrospun ha-PLGA constructs for no longer than 4 to 8 weeks [56][57][58][59][60][61][62]. The changes in scaffolds' morphology, mass, liquid uptake, molecular weight, and distribution, as well as their mechanical properties, together with the changes in pH and conductivity, were investigated systematically.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, in this study for the first time to our knowledge, electrospun ha-PLGA scaffolds, designed for tendon TE, were subjected to hydrolytic degradation under di-H 2 O and PBS conditions at 37 • C and evaluated for up to 20 weeks. Of note, tendons regenerate at a slow healing rate, which necessitated performing the degradation study up to 20 weeks, compared to most other studies that usually conducted similar experiments on electrospun ha-PLGA constructs for no longer than 4 to 8 weeks [56][57][58][59][60][61][62]. The changes in scaffolds' morphology, mass, liquid uptake, molecular weight, and distribution, as well as their mechanical properties, together with the changes in pH and conductivity, were investigated systematically.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to functionalizing the surface of electrospun fibers, therapeutic molecules such as small-molecule drugs, proteins, and nucleic acids (e.g., DNA, miRNA, and siRNA) can be immobilized onto the surface or encapsulated within electrospun fibers to allow for prolonged, local therapeutic delivery [ 154 , 155 ]. Small-molecule drug-loaded electrospun fibers can be utilized to alter Schwann cell activity or affect the Schwann cell maturation state [ 156 , 157 ]. For example, Bhutto et al fabricated an aligned poly ( l -lactic acid-co-caprolactone)/silk fibroin fiber mesh loaded with vitamin B5 via blend electrospinning and observed greater Schwann cell proliferation and dispersion across the entirety of the scaffold compared to unloaded control fibers.…”
Section: Peripheral Nervous System Glia and Electrospun Fibersmentioning
confidence: 99%
“…In another study, Puhl et al found that the incorporation of the drug fingolimod hydrochloride, known to shift Schwann cells to an immature repair state—into highly aligned PLGA electrospun fibers—increased Schwann cell migration compared with control PLGA fibers. Additionally, the sustained release of fingolimod reduced the Schwann cell expression of mature, promyelinating markers [ 157 ]. Following injury or in a disease state, the PNS can be subjected to various forms of stress that can lead to increased Schwann cell death [ 158 ].…”
Section: Peripheral Nervous System Glia and Electrospun Fibersmentioning
confidence: 99%
“…There have been numerous subsequent studies that have used a wide variety of materials to explore what topographical or biochemical features are best suited to support directional growth of neurites as well as the alignment of glial cells that, in turn, would support such growth. This literature is extensive and has been reviewed by several investigators [154,156,157,166,167]. One of the overarching conclusions that can be gleaned from these studies is that aligned substrates, whatever means by which they are produced, exert compelling directional cues for growing neurites.…”
Section: Reconstruction Of Tissue Geometry To Promote Regenerationmentioning
confidence: 99%